THE EFFECT OF INTELLIGENCE AND ACADEMIC SUCCESS ON SELFPERCEPTIONS OF PRIMARY SCHOOL STUDENTS - (:unkn) unknown (My University, 2019)
This study examined the relationship between intelligence levels, self-perception, and theacademic achievement of fourth-grade primary school students. The study was carried out with36 students in a state school in Istanbul, Turkey. A survey was administered with ademographic form containing the students’ Turkish and Mathematics course achievementscores and personal information, the Wechsler Intelligence Scale for Children-Revised-WISCR,and the Piers-Harris Children’s Self Concept Scale. The findings indicated that neither selfperceptionnor the academic achievement is related to gender. Student intelligence scores werestrongly related to mathematics scores and weakly related to Turkish scores. Achievementscores for Turkish and mathematics were positively associated with the information subtestscores for long-term memory in the verbal section of WISC-R. Achievement scores for themathematics course predicted the digit symbol subtest scores (psychomotor coordination andspeed) in the performance section of WISC-R. Intelligence and academic success had nosignificant relationship with the children’s self-concepts.
Keywords: Eğitim, Eğitim Araştırmaları